2015
DOI: 10.1002/aur.1460
|View full text |Cite
|
Sign up to set email alerts
|

“Put Myself Into Your Place”: Embodied Simulation and Perspective Taking in Autism Spectrum Disorders

Abstract: Embodied cognition theories hold that cognitive processes are grounded in bodily states. Embodied processes in autism spectrum disorders (ASD) have classically been investigated in studies on imitation. Several observations suggested that unlike typical individuals who are able of copying the model's actions from the model's position, individuals with ASD tend to reenact the model's actions from their own egocentric perspective. Here, we performed two behavioral experiments to directly test the ability of ASD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
66
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(82 citation statements)
references
References 66 publications
(128 reference statements)
7
66
3
Order By: Relevance
“…It also implies that presenting figures in the OBT task tilted by 90° (e.g., May & Wendt, 2012) does not offer a way to control for spatial compatibility. This implies that spatial compatibility may contribute to the results of experiments that have attempted to rule out compatibility effects in this way (e.g., Conson et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It also implies that presenting figures in the OBT task tilted by 90° (e.g., May & Wendt, 2012) does not offer a way to control for spatial compatibility. This implies that spatial compatibility may contribute to the results of experiments that have attempted to rule out compatibility effects in this way (e.g., Conson et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A preliminary study with a very small sample links improving physical 'motor' perspective taking (facilitating an actor performing a physical action) with increased language of mental states and mental perspective-taking (Studenka, Gillam, Hartzheim, & Gillam, 2017). The ability to mentally 'put yourself in another's place', to simulate their visual perspective, is known to be challenging for individuals with ASC (Conson et al, 2015;Pearson, Ropar, & Hamilton, 2013) and is suggested, like mentalizing, to rely on alternative processing strategies. Investigation of the neural mechanisms of these strategies is of high research importance.…”
mentioning
confidence: 99%
“…Autism spectrum disorder patients have been shown to be less susceptible to feel ownership of a rubber hand (Palmer et al, 2015). Also, other experimental paradigms reported an altered sense of embodiment over the own body in the case of autistic patients (Conson et al, 2015), as their findings suggest that these patients rely less on one's own information to infer states over another person or external object. On the other hand, schizophrenic patients perceive other-generated actions as their own in a bimanual interference task, thus presenting an increased sense of agency (Garbarini et al, 2016).…”
Section: Embodiment and Variabilitymentioning
confidence: 91%